Cost‐effectiveness of zoledronic acid and strontium‐89 as bone protecting treatments in addition to chemotherapy in patients with metastatic castrate‐refractory prostate cancer: results from the TRAPEZE trial (ISRCTN 12808747). (10th July 2016) - Andronis, Lazaros; Goranitis, Ilias; Pirrie, Sarah; Pope, Ann; Barton, Darren; Collins, Stuart; Daunton, Adam; McLaren, Duncan; O'Sullivan, Joe M.; Parker, Chris; Porfiri, Emilio; Staffurth, John; et al.
Abstract : Objective: To evaluate the cost‐effectiveness of adding zoledronic acid or strontium‐89 to standard docetaxel chemotherapy for patients with castrate‐refractory prostate cancer (CRPC). Patients and methods: Data on resource use and quality of life for 707 patients collected prospectively in the TRAPEZE 2 × 2 factorial randomised trial (ISRCTN 12808747) were used to assess the cost‐effectiveness of i) zoledronic acid versus no zoledronic acid (ZA vs. no ZA), and ii) strontium‐89 versus no strontium‐89 (Sr89 vs. no Sr89). Costs were estimated from the perspective of the National Health Service in the UK and included expenditures for trial treatments, concomitant medications, and use of related hospital and primary care services. Quality‐adjusted life‐years (QALYs) were calculated according to patients' responses to the generic EuroQol EQ‐5D‐3L instrument, which evaluates health status. Results are expressed as incremental cost‐effectiveness ratios (ICERs) and cost‐effectiveness acceptability curves. Results: The per‐patient cost for ZA was £12 667, £251 higher than the equivalent cost in the no ZA group. Patients in the ZA group had on average 0.03 QALYs more than their counterparts in no ZA group. The ICER for this comparison was £8 005. Sr89 was associated with a cost of £13 230, £1365 higher than no Sr89, and a gain of 0.08 QALYs compared to no Sr89. The ICER for Sr89 was £16 884. The probabilities of ZA and Sr89 being cost‐effective were 0.64 and 0.60, respectively. Conclusions: The addition of bone‐targeting treatments to standard chemotherapy led to a small improvement in QALYs for a modest increase in cost (or cost‐savings). ZA and Sr89 resulted in ICERs below conventional willingness‐to‐pay per QALY thresholds, suggesting that their addition to chemotherapy may represent a cost‐effective use of resources.